Ce qui est abusif au sens de l'article 8 de la Charte canadienne lors de la recherche de preuves - Auger, Bernard (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
In determining whether legislation permitting search and seizure properly meets the requirements of section 8 of the Canadian Charter of Rights and Freedoms, the courts have been obliged to balance the right of the individual to be secure against unreasonable search and seizure with the right of the state to ensure compliance with the law. In Hunter v. Southam, the Supreme Court of Canada established the minimum criteria of reasonable search and seizure for the purposes of section 8. The liberal approach adopted by the Supreme Court raises an important question : Should the same criteria apply to administrative statutes empowering bodies to conduct inquiries and inspections ? The author compares section 8 of the Charter with the American 4th Amendment, examining the requirement for search warrants in the light of Canadian cases. He then examines and discusses the case law concerning the applicability of section 8 to statutory provisions relating to the production of documents and the standard of reasonableness that should apply to these situations.